Kontrol Ketinggian Air pada Budidaya Ikan dan Tanaman Yumina Bumina Menggunakan Metode Fuzzy Takagi-Sugeno - Tegar Assyidiqi Nugroho; Tibyani Tibyani; Rekyan Regasari Mardi Putri (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The water level is less than ideal can lead to a lack of free areas and the lack of oxygen in the water that results in unhealthy and dying fish and damage plant roots. In addition to the pool water at open area also affected by the rain water can cause the water in the pond overflowed, the water becomes acid can also lead to impaired fish health. Based on the issue of his height control system of water on fish farming and plant yumina-bumina using fuzzy method of takagi-sugeno. This research uses 2 parameter i.e. altitude and rainfall as input that is controlled by the arduino and gives the output form control pumps to fill, reduce or replace the pool water. To define the output method using fuzzy takagi-sugeno. At the end of the study it can be concluded the system is able to control the height of the water in accordance with the initial draft.